Evaluation of Performance of Seed Coating Formulation for Direct Seeded Rice (DSR) in Dry and Puddled Conditions - K RAJA; K MALARKOD; C VANITHA; S MANONMAN; M KATHIRAVAN; V VAKESWARAN; K NATARAJAN; C MENAKA; V VIJAYALAKSHMI; R UMARANI (Seed Research, 2025)
Direct Seeded Rice (DSR) is an agronomic practice wherein seeds are sown directly into the field, circumventing the conventional method of transplanting. Given the critical role of early crop establishment in DSR, enhanced seed germination and seedling vigor are imperative for achieving optimal crop performance. To this end, a study was undertaken during 2023–2024 growing season to assess the impact of the TNAU seed coating formulation, TNAU Vidhai Amirtham, on crop growth and yield under DSR conditions. The rice seeds were treated with TNAU Vidhai Amirtham @ 25 ml / kg and sown under DSR dry condition as well as puddled condition. The results showed that the rice seeds treated with TNAU Vidhai Amirtham @ 25 ml / kg has recorded higher field emergence (95.5%), root volume (39.5 cm3), number for productive tillers (19.0), plant height (112.4 cm), panicle length (25.9 cm), number of seeds / panicle (199.10) and seed yield (4309 kg / ha) than the untreated control under direct seeded unpuddled dry condition. Correspondingly, the field emergence (95.6%), root volume (41.0 cm3), number for productive tillers (31.5), plant height (118.7 cm), panicle length (26.7 cm), number of seeds /panicle (284.0) and seed yield (6375 kg / ha) were higher in the TNAU Vidhai Amirtham treated seeds under puddled condition compared to untreated control. Thus, rice seed treatment with TNAU Vidhai Amirtham @ 25 ml / kg can be followed for the better plant growth and yield under DSR system.